The Effect of Brushing Teeth on the Debris Index in Elementary School Children - vania khaindira; Sri Hidayati utomo; Silvia Prasetyowati; Ida Chairanna Mahirawatie utomo (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The average debris index in grade II students of SDN 225 Gresik is included in the bad category. The poor level of debris index for grade II students of SDN 225 Gresik is caused by several factors, including the way they brush their teeth. Debris is food debris that sticks to teeth and gingivas. Brushing your teeth is one of the easiest and cheapest preventive efforts to prevent tooth decay. Good brushing skills can also affect dental and oral hygiene and health, including in reducing food debris, plaque, and other dental problems. The purpose of this study is to determine the effect of brushing teeth on the debris index of grade II students of SDN 225 Gresik. This type of research is an analytical research with a cross sectional design, with a sample of 30 grade II students at SDN 225 Gresik. The data collection instruments used are observation sheets and examination sheets. The data analysis technique uses the Chi-Square test. The results of the research on how to brush the teeth of grade II students at SDN 225 Gresik are in the bad category, which is 53%. The debris index of grade II students at SDN 225 Gresik is in the medium category, which is 47%. The results of this study obtained a p value of 0.000 or a p value of significance below α (0.05). There is an effect of brushing teeth on the debris index of grade II students of SDN 225 Gresik. There is an effect between the way you brush your teeth on the debris index of grade II students of SDN 225 Gresik.